A Comprehensive Overview of the Physical Health of the Adolescent Brain Cognitive Development Study Cohort at Baseline - Palmer, Clare E.; Sheth, Chandni; Marshall, Andrew T.; Adise, Shana; Baker, Fiona C.; Chang, Linda; Clark, Duncan B.; Coronado, Clarisa; Dagher, Rada K.; Diaz, Vanessa; Dowling, Gayathri J.; Gonzalez, Marybel R.; et al. (Frontiers in Pediatrics, 2021)
Physical health in childhood is crucial for neurobiological as well as overall development, and can shape long-term outcomes into adulthood. The landmark, longitudinal Adolescent Brain Cognitive Development StudySM (ABCD study®), was designed to investigate brain development and health in almost 12,000 youth who were recruited when they were 9-10 years old and will be followed through adolescence and early adulthood. The overall goal of this paper is to provide descriptive analyses of physical health measures in the ABCD study at baseline, including but not limited to sleep, physical activity and sports involvement, and body mass index, and how these measures vary across demographic groups. This paper outlines how the physical health of the ABCD sample corresponds with that of the US population and highlights important avenues for health disparity research. This manuscript will provide important information for ABCD users and help guide analyses investigating physical health as it pertains to adolescent and young adult development.